Pelaksanaan dan Pengelolaan BUMDES di Desa Sentang - Siagian, Friska Febrianti br; Rahmat, Rahmat; Adly, Adly; Alverina, Lufita; Harahap, Togu Parlindungan (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to investigate the establishment and management of village-owned enterprises (BUMDES) as a means of enhancing the income of rural communities. To support the attainment of these objectives, the author employs a normative juridical research method, utilizing a statutory and conceptual approach. The findings of the study indicate that the procedures for creating and managing BUMDES for the purpose of increasing rural community income in the economic sector have been effective. This is reinforced by the fact that BUMDES serves as a pivotal driver of the village economy, functioning as a revenue generator for the village (PADes) and as a tool to expedite the enhancement of the well-being of rural communities. The specific regulations governing this matter are outlined in ministerial regulations, rather than in laws, as ministerial regulations serve as implementing guidelines. Consequently, there are normative issues, including gaps in legal norms, which have implications for their practical implementation in the field.